Evolution of C-Reactive Protein - Pathak, Asmita; Agrawal, Alok (Frontiers in Immunology, 2019)
C-reactive protein (CRP) is an evolutionarily conserved protein. From arthropods to humans, CRP has been found in every organism where the presence of CRP has been sought. Human CRP is a pentamer made up of five identical subunits which binds to phosphocholine (PCh) in a Ca2+-dependent manner. In various species, a protein is defined as CRP if it has any two of the following three characteristics: First, it is a cyclic oligomer of almost identical subunits of molecular weight 20-30 kDa. Second, it binds to PCh in a Ca2+-dependent manner. Third, it exhibits immunological cross-reactivity with human CRP. In the arthropod horseshoe crab, CRP is a constitutively expressed protein, while in humans, CRP is an acute phase plasma protein; a component of the acute phase response. As the nature of CRP gene expression evolved from a constitutively expressed protein in arthropods to an acute phase protein in humans, the definition of CRP became distinctive. In humans, CRP can be distinguished from other homologous proteins such as serum amyloid P, but this is not the case for most other vertebrates and invertebrates. Literature indicates that the binding ability of CRP to PCh is less relevant than its binding to other ligands. Human CRP displays structure-based ligand-binding specificities, but it is not known if that is true for invertebrate CRP. During evolution, changes in the intra-disulfide and inter-disulfide bonds and changes in the glycosylation status of CRP may be responsible for different structure-function relationships of CRP in various species. More studies of invertebrate CRP are needed to understand the reasons behind such evolution of CRP. Also, CRP evolved as a component of and along with the development of the immune system. It is important to understand the biology of ancient CRP molecules because the knowledge could be useful for immunodeficient individuals.